2018
DOI: 10.1016/j.antiviral.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Porcine epidemic diarrhea virus papain-like protease 2 can be noncompetitively inhibited by 6-thioguanine

Abstract: Porcine epidemic diarrhea virus (PEDV) is a coronavirus (CoV) discovered in the 1970s that infects the intestinal tract of pigs, resulting in diarrhea and vomiting. It can cause extreme dehydration and death in neonatal piglets. In Asia, modified live attenuated vaccines have been used to control PEDV infection in recent years. However, a new strain of PEDV that belongs to genogroup 2a appeared in the USA in 2013 and then quickly spread to Canada and Mexico as well as Asian and European countries. Due to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Virtual screening of the compounds against of the targets used was done using the AutoDock Vina in PyRx [ 80 ] on Windows 10-supported Dell system (processor: Intel(R) Core(TM) i7-8550U CPU @ 1.80 GHz with a 64-bit operating system, ×64-based processor, a memory of 8.00 GB). First, the docking protocol was validated by docking cocrystallized ligands to the protein keeping the docking parameters default except for the sphere around the binding site, which was set to 15 Å. Validation was also done by comparing the best-ranked compounds conformation relative to the crystallized ligand by root-mean-square deviation (RMSD) [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…Virtual screening of the compounds against of the targets used was done using the AutoDock Vina in PyRx [ 80 ] on Windows 10-supported Dell system (processor: Intel(R) Core(TM) i7-8550U CPU @ 1.80 GHz with a 64-bit operating system, ×64-based processor, a memory of 8.00 GB). First, the docking protocol was validated by docking cocrystallized ligands to the protein keeping the docking parameters default except for the sphere around the binding site, which was set to 15 Å. Validation was also done by comparing the best-ranked compounds conformation relative to the crystallized ligand by root-mean-square deviation (RMSD) [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was identified as an allosteric inhibitor of SARS-CoV and a competitive inhibitor of MERS-CoV [ 69 ]. The cysteine protease inhibitor N-Ethylmaleimide (NEM) that covalently modifies the active-site Cys inhibited SARS-CoV, but was a poor inhibitor of MERS-CoV PLpro [ 70 , 71 ].…”
Section: A Hindsight View Of Developing Cov Plpro Inhibitorsmentioning
confidence: 99%
“…Additionally, 6-mercaptopurine (6MP) and 6-thioguanine (6TG) have been widely used in cancer treatment. They are competitive slow-binding inhibitors that form hydrogen bonds with the catalytic triads of SARS-CoV and MERS-CoV PLpro [ 70 , 71 ]. Disulfiram, a drug that has been used in alcohol aversion therapy since 1951, is an irreversible covalent inhibitor for SARS-CoV PLpro (competitive (or mixed)) and MERS-CoV (noncompetitive) [ 72 ].…”
Section: A Hindsight View Of Developing Cov Plpro Inhibitorsmentioning
confidence: 99%
“…In another study, Galanthus nivalis agglutinin and nelfinavir were shown to synergistically exert an antiviral effect on FCoVs in vitro [ 179 ]. The chemotherapeutic drug, 6-thioguanine, was found to noncompetitively inhibit the PEDV papain-like protease 2 [ 180 ]. Interestingly, 3CLpro inhibitor resistant MHV mutants were shown to be attenuated for replication and pathogenesis in mice, revealing a low genetic barrier but high fitness cost of resistance for CoVs [ 181 ].…”
Section: Therapeutics Against Sars-cov-2 and The Animal Coronavirumentioning
confidence: 99%